SOCIOCULTURAL ENVIRONMENT AND ITS IMPORTANCE IN THE DEVELOPMENT OF A CHILD OF PRESCHOOL AGE - Mahkamova, Shohida (Журнал иностранных языков и лингвистики, 2021)
The sociocultural environment is considered as a set of purposefully created conditions that should ensure the process of development and self-development of a child. On the one hand, this is a space for the development and self-determination of the child, and on the other hand, these are pedagogical influences aimed at the development of the child's personality.